Urban Sufism: Religiousity and Identity Construction of Urban Muslim Community - Inayatul Ulya (Jurnal Hikmatuna, 2019)
Urban sufism is a phenomenon that shows the hijrah representation of urban Muslim communities and the rise of religion in the public sphere. The religious expression displayed by urban Muslim communities is a form of religious accommodation towards modernity. Even religion can be a living solution for modern society. This article explains that exchanging folk is even an identity sought by urban Muslim communities. Their participation in Sufism education is a new form for constructing their religious identity. Referring to Peter L. Berger's construction theory that religion in a cultural context is a product constructed by humans. So that there is a dialectical process between religion and society. The dialectical process goes through three stages, namely externalization, objectification and internalization. The results of the dialectics of religion and culture make Sufism the religious identity of urban Muslim communities. This religious identity is needed by urban Muslim communities both in their roles as individuals and as part of social communities. As individuals, religious identity is needed to fulfill spiritual needs towards self-righteousness and as members of social groups in society, religious identity is needed to strengthen the existence of urban Muslim communities by presenting Sufism with new styles that are more accommodating to modernity.